IMPLIKASI PENGGUNAAN CHAT GPT TERHADAP LITERASI MATEMATIKA MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS PENDIDIKAN INDONESIA - Alifia Salsabila; Alya Putri Ramadhani; Fathma Nailal Husna (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The use of Chat GPT has potential implications for mathematical literacy in students. This case study focused on mathematics education students to find out the relationship between Chat GPT and Mathematics literacy and used a descriptive qualitative approach. Chat GPT is an artificial intelligence-based technology, can help in answering math questions and providing the necessary information. In addition, the use of Chat GPT can also improve the quality of research articles in the field of mathematics education. However, there are negative impacts that need to be considered, such as dependence on technology and the potential replacement of human labor. Therefore, the use of Chat GPT in the context of mathematical literacy needs to be further expanded to comprehensively understand its positive and negative impacts. This study is expected to contribute to the understanding of Chat GPT's capabilities and provide input for educators and researchers in utilizing it as a tool in writing research articles and learning mathematics.